Chapter62006solutions

# Chapter62006solutions - Chapter 6 Test December 5 2006 Name...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Chapter 6 Test December 5, 2006 Name x i 2y j z â€¡ jsec 3 x tan 3 x - csc Ã„Ã„Ã„Ã„Ã„ z dx k 4{ x w = Ã„Ã„Ã„Ã„Ã„ and 4 dw = dx 4 1 ixy jz Ã„Ã„Ã„Ã„Ã„ sec H3 xL + 4 cot j Ã„Ã„Ã„Ã„Ã„ z + C k4{ 3 2. Evaluate â€¡ sin-1 H2 xL dx 0 1 Ã„Ã„Ã„Ã„Ã„ 2 xy i j z 1. Evaluate â€¡ jsec 3 x tan 3 x - csc2 Ã„Ã„Ã„Ã„Ã„ z dx k 4{ = so x i 2y j z Ã† u = 3 x and â€¡ Hsec 3 x tan 3 x L dx - â€¡ jcsc Ã„Ã„Ã„Ã„Ã„ z dx k 4{ 1 1 = Ã„Ã„Ã„Ã„Ã„ sec u Ã† Ã„Ã„Ã„Ã„Ã„ â€¡ Hsec u tan u L du - 4 â€¡ Icsc2 wM dw 3 3 1 Ã„Ã„Ã„Ã„Ã„ du = dx 3 + 4 cot w + C or u = sin-1 H2 xL -1 â€¡ sin H2 xL dx Ã† so 1 "################ ### ### Ax sin-1 H2 xL + Ã„Ã„Ã„Ã„Ã„ 1 - 4 x2 2 -1 1 Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ x sin-1 H2 xL + Ã„Ã„Ã„Ã„Ã„ â€¡ w 2 dw 4 1 Ã„Ã„Ã„Ã„Ã„ 2 D 0 = 2x = x sin-1 H2 xL - Â· Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„ dx Ã„Ã„Ã„Ã„ "################ 2 ###### 1 - 4x = 2 du = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„ dx Ã„Ã„Ã„Ã„ "################ 2 ###### 1 - 4x and v=x dv = dx and using and choosing w = 1 - 4 x2 , dw = - 8 x dx â€¡ u dv = uv - â€¡ v du or we have 1 Ã„Ã„Ã„Ã„Ã„ dw = - 2 x dx 4 so 3. Solve the initial value problem. Support your answer by overlaying your solution on a slope field for the dy i -p y z j differential equation. Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = y sin x y j Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ z = 1 k2{ dx 1z i1 ipy j z j Ã„Ã„Ã„Ã„Ã„ j Ã„Ã„Ã„Ã„Ã„ z + 0y - i0 + Ã„Ã„Ã„Ã„Ã„ y z j z jjz z j z j z j z j 2{ k { k2 k2{ 1 1 Ã„Ã„Ã„Ã„Ã„ x sin-1 H2 xL + Ã„Ã„Ã„Ã„Ã„ w 2 + C 2 = or p 1 Ã„Ã„Ã„Ã„Ã„ - Ã„Ã„Ã„Ã„Ã„ 4 2 1 "################ ###### x sin-1 H2 xL + Ã„Ã„Ã„Ã„Ã„ 1 - 4 x2 + C 2 2 1 âˆ’Ï€ âˆ’ Ï€ 2 âˆ’1 Ã† Ï€ 2 1 dy â€¡ Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ dx y dx or D=1 Ï€ ln Â» y Â» = - cos x + C so dy Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = y sin x dx Ã† 1 dy Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = sin x y dx so -p -cos I Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ M 2 1 = De = D H1L Â» y Â» = eC e-cos x so y = Â± eC e-cos x and = â€¡ sin x dx Ã† or y = D e-cos x 1 â€¡ Ã„Ã„Ã„Ã„Ã„ dy y = â€¡ sin x dx and so y = e-cos x i -p y j z y j Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ z = 1 k2{ 2 4. Evaluate â€¡ 3 x3 2x dx 3 x2 dx â€¡ 3x 2 so u=w First, 2 x2 H3 x dxL â€¡x2 du = dw w = x2 , so dw = 2 x dx or 3 Ã„Ã„Ã„Ã„Ã„ dw = 3 x dx 2 and = dv = 2w dw 3 Ã„Ã„Ã„Ã„Ã„ â€¡ w 2w dw 2 and using integration by parts, we get and 2 3 x2 2x Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ 2 ln 2 3 Ã„Ã„Ã„Ã„Ã„ â€¡ w 2w dw 2 i 2y 3 j2x z j z k { Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ 2 2 Hln 2L = 3 x2 dx â€¡ 3x 2 3 Ã„Ã„Ã„Ã„Ã„ 2 1 v = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ 2w Ã„ ln 2 3 Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ w 2w Ã„ 2 ln 2 - 5. Use separation of variables to solve the following differential equation : cos y Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ dy = - 4 x dx Ã„Ã„ sin2 y 1 â€¡ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ du = - â€¡ 4 x dx u2 1 i y j y = sin-1 j Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ z Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ z j z j 2 + Cz k 2x { cos y Ã„Ã„ â€¡ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ dy = â€¡ - 4 x dx sin2 y p 1 i y j Ã„Ã„Ã„Ã„Ã„ = sin-1 j Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„ z, Ã„Ã„Ã„Ã„ z j z j z 2 k2 + C{ -1 Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = - 2 x2 + C1 u so 3 Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„ 2w Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ 2 Hln 2L2 +C Ã† - +C 1 y i1 j Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ w 2w - Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ z jÃ„ Ã„ â€¡ 2w dwz z j z j ln 2 { k ln 2 2 = â€¡ x2 2x H3 x dxL or dy - 4 x sin2 y Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„ dx cos y Let Ã† and Ã† Ã† Ã† u = sin y, then Ã† p y H1L = Ã„Ã„Ã„Ã„Ã„ 2 du = cos y dy so and 1 Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = 2 x2 + C Ã„ sin y C = -1 and 6. Evaluate u = x3 + 1 du = 3 x2 dx 3 â€¡ Ix + 1M cos 2 x dx 1 v = Ã„Ã„Ã„Ã„Ã„ sin 2 x 2 dv = cos 2 x dx 1 i y j y = sin-1 j Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ z Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ z j z j 2 - 1z k 2x { 1 sin y = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ 2 x2 + C so Use integration by parts on -1 y z j 2 2i and use integration by parts on â€¡ x cos 2 x dx, so z j â€¡ x Hsin 2 xL dx = x j Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ cos 2 xz + â€¡ x cos 2 x dx, z { k2 1 1 1 1 1 u = x, du = dx, dv = cos 2 x dx, and v = Ã„Ã„Ã„Ã„Ã„ sin 2 x Ã† â€¡ x cos 2 x dx = Ã„Ã„Ã„Ã„Ã„ x sin 2 x - Ã„Ã„Ã„Ã„Ã„ â€¡ sin 2 x dx = Ã„Ã„Ã„Ã„Ã„ x sin 2 x + Ã„Ã„Ã„Ã„Ã„ cos H2 xL 2 2 2 2 4 1 1 y i -1 z j So, â€¡ x2 Hsin 2 xL dx = x2 j Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ cos 2 xz + Ã„Ã„Ã„Ã„Ã„ x sin 2 x + Ã„Ã„Ã„Ã„Ã„ cos H2 xL, and z j 2 4 { k2 1 3 i i -1 1 1 y y 3 z z jj = Ix3 + 1M Ã„Ã„Ã„Ã„Ã„ sin 2 x - Ã„Ã„Ã„Ã„Ã„ jx2 j Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ cos 2 xz + Ã„Ã„Ã„Ã„Ã„ x sin 2 x + Ã„Ã„Ã„Ã„Ã„ cos H2 xLz + C or jj z z â€¡ Ix + 1M cos 2 x dx jj z z 2 4 2 2k k 2 { { 3 3 3 Ix3 + 1M sin H2 xL + Ã„Ã„Ã„Ã„Ã„ x2 cos H2 xL - Ã„Ã„Ã„Ã„Ã„ x sin H2 xL - Ã„Ã„Ã„Ã„Ã„ cos H2 xL + C of course, you could also use tabular integration here ! 4 4 8 7. Evaluate 2 â€¡ log3 x dx 1 3 2 â€¡ x Hsin 2 xL dx Ã† 3 â€¡ Ix + 1M cos 2 x dx = u = x2 , du = 2 x dx, 1 Ix3 + 1M Ã„Ã„Ã„Ã„Ã„ sin 2 x 2 3 Ã„Ã„Ã„Ã„Ã„ â€¡ x2 Hsin 2 xL dx, 2 -1 dv = sin 2 x dx, and v = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ cos2x 2 - 3 log3 x2 dx = 2 â€¡ log3 x dx Ã† â€¡ 1 1 3 1 u = log3 x, du = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ dx, Ã„ x ln 3 dv = dx, v = x Ã† x 1 x Ã„ Ã„ Ã„ â€¡ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ dx = â€¡ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ dx = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ , so x ln 3 ln 3 ln 3 8. Evaluate u = e2 x , u = e2 x , 2 x sin x dx â€¡e 3 x3 Ã„ 2 â€¡ log3 x dx = 2Ax Hlog3 xL - Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ E ln 3 1 1 3 1y i j = 2A3 - Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ - j0 - Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ zE Ã„ Ã„z j z j ln 3 k ln 3 { x Ã„ â€¡ log3 x dx = x Hlog3 xL - â€¡ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ dx x ln 3 = 4 6 - Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„ ln 3 du = 2 e2 x dx, dv = sin x, v = - cos x, du = 2 e2 x dx, dv = cos x, v = sin x, so so Let I = â€¡ e2 x sin x dx, then I = - e2 x cos x + 2 e2 x sin x - 4 I I = - e2 x cos x + 2 Je2 x sin x - 2 â€¡ sin x e2 x dxN = - e2 x cos x + 2Ae2 x sin x - 2 IE Ã† - e2 x cos x + 2 e2 x sin x I = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„ , so â€¡ e2 x sin x dx = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ 5 2 x cos x dx = e2 x sin x - 2 sin x e2 x dx â€¡e â€¡ 2 x sin x dx = - e2 x cos x + 2 e2 x cos x dx â€¡e â€¡ Ã† use IBP again or -1 2 Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ e2 x cos x + Ã„Ã„Ã„Ã„Ã„ e2 x sin x + C 5 5 9. Evaluate u = ln x so 1 Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ â€¡ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ dx 2 x Hln xL3 1 dx = Ã„Ã„Ã„Ã„Ã„ dx x so 10. The half life of Polonium - 210 is 138 days. If we currently have 10 grams, how long ago did we have 34 grams? y0 Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = y0 Hec L138 2 5 138 ln Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ 17 t = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ 1 ln Ã„Ã„Ã„Ã„Ã„ 2 1 Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ â€¡ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ dx 2 x Hln xL3 Ã† 1 Ã„Ã„Ã„Ã„Ã„ â€¡ u-3 du 2 = -1 Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ u-2 + C 4 or -1 Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„ + C Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ 4 Hln xL2 y = y0 ec t if we plug in t = 138, half of the original will remain, so so, 11. Finals start in one week ! Some students Hnot youL are slow in getting ready for their finals, and the rate at dP 0.3 i Py j which the MV population is prepared can be modeled by the differential equation Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ P j5 - Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ z. If Ã„ Ã„z j z dt 5 500 { k M - P0 dP k M Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ P0 = 2, Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ P HM - PL and P = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„ , A = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„ , Ht is measured in daysL Ã„Ã„Ã„Ã„ P0 dt M 1 + A e-k t HaL Find a solution to this differential equation. HbL Find how long it will take for all students at MV H2400 of themL to be prepared for their final exams. tÃ„ i 1 y Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ jz 10 = 34 j Ã„Ã„Ã„Ã„Ã„ z 138 jz z k2{ Ã† tÃ„ 5 i 1 y Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ jz Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = j Ã„Ã„Ã„Ã„Ã„ z 138 jz jz 17 k 2 { Ã† 5 t 1 ln Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ ln Ã„Ã„Ã„Ã„Ã„ Ã„ 17 138 2 Ã† = 1 Ã„ i 1 y Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ jz Ã† ec = j Ã„Ã„Ã„Ã„Ã„ z 138 jz jz k2{ 138 Hln 17 - ln 5L Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ days ago Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ ln 2 dP 0.3 i 1 y i i j HaL Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ j Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ z jH500L P j5 Ã„ j Ã„ zj j zj j j z dt 5 k 500 { k k 2500 - 2 A = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = 1249 Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ so 2 2500 HbL 2400 = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„ Ã† 1 + 1249 e-0.3 t so e-0.3 t 1 = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ 24 H1249L or P yy Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ zz Ã„ zz zz 500 {{ 2400 I1 + 1249 e-0.3 t M = 2500 e0.3 t = 24 H1249L Ã† dP 0.3 Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ P H2500 - PL, Ã„ dt 2500 2500 P = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„ 1 + 1249 e-0.3 t Ã† Ã† so k = 0.3, M = 2500, P0 = 2, and 12. DeRuiter has moved into his "new" house, but there' s no heat ! Assume that he brings his hot chocolate into the house at a temperature of 120 Â° F, and the interior or the house is 55 Â° F. After 15 minutes, the chocolate has cooled to 100 Â° F. How much longer will it take for the hot chocolate to cool to 70 Â° F ? dT i j These may help : Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = - k HT - T L and T - T = HT - T L e-k t y z j z j z s s s j z 0 dt k { t i 9 y Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ j z T - 55 = 65 j Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ z 15 j z k 13 { 9 T - 55 = H65L Ie-kt M Ã† 100 - 55 = 65 Ie-k M15 Ã† 45 = 65 Ie-k M15 Ã† Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = Ie-k M15 Ã† 13 Ã† t i 9 y Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ j z 15 = 65 j Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ z 15 j z j z k 13 { Ã† 3 t 9 ln Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ ln Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ 13 15 13 Ã† t = 1 i 9 y Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ z j e-k = j Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ z 15 z j j k 13 { 0.3 t = ln H29976L 2500 1 + 1249 e-0.3 t = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„ 2400 Ã† Ã† 10 t = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ ln H29976L days 3 1 1249 e-0.3 t = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ 24 so 13. Evaluate u = csc x du = - csc x cot x 3 â€¡ csc x dx i 15 H ln 13 - ln 3L j Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ - 15y minutes z j z Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ j z z j k ln 13 - ln 9 { v = - cot x dv = csc2 x so since cot2 x = csc2 x - 1 we can write our expression as - csc x cot x - â€¡ csc3 x dx + â€¡ csc x dx that original integral A, we can write multiply by csc x - cot x Notice that the original integral is repeat in this expression, so if we call Now, to deal with the last integral, we or in numerator and denominator, A = - csc x cot x - A + â€¡ csc x dx so - csc x cot x - â€¡ csc x Icsc2 x - 1M dx 3 2 â€¡ csc x dx = - csc x cot x - â€¡ csc x cot x dx or csc2 x - csc x cot x A = - csc x cot x - A + â€¡ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„ dx Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„ and w = csc x - cot x csc x - cot x 1 Ã† A = - csc x cot x - A + â€¡ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ dw Ã† 2 A = - csc x cot x + ln Â» w Â» w Æ’ Æ’ Æ’ Æ’ -1 1 Æ’ Æ’ Æ’ Æ’ A = Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ csc x cot x + Ã„Ã„Ã„Ã„Ã„ ln Æ’ csc x - cot x Æ’ + C Æ’ Æ’ Æ’ Æ’ Æ’ Æ’ Æ’ Æ’ Æ’ Æ’ 2 2 14. Use EulerÂ¢ s Method to numerically solve the initial value problem interval - 1 Â£ x Â£ 2 starting at x0 = - 1 with dx = 1. yn + 1 = yn + f Hxn , yn L Dx y1 = 1 + H- 1 + 2L H1L = 2, Ã† y2 = 2 + H0 + 4L H1L = 6, Ã† y3 = 6 + H1 + 12L H1L = 19, Ã† and H0, 2L y0 = 1, yÂ¢ = x + 2 y, csc x - cot x A = - csc x cot x - A + â€¡ csc x Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ dx Ã„Ã„Ã„Ã„Ã„Ã„Ã„Ã„ csc x - cot x so so dw = I- csc x cit x + csc2 xM dx H2, 19L H1, 6L and the initial point is H- 1, 1L y H- 1L = 1, on the ...
View Full Document

## This note was uploaded on 08/29/2010 for the course MATH 44323 taught by Professor Anderson during the Spring '09 term at Berkeley.

Ask a homework question - tutors are online